2021
DOI: 10.3390/jcm10020361
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Quantitative Characterization of Post-Transplant Lymphoproliferative Disorder Morphological Subtypes with [18F]FDG PET/CT

Abstract: Background: Post-transplant lymphoproliferative disorder (PTLD) is a complication of organ transplantation classified according to the WHO as nondestructive, polymorphic, monomorphic, and classic Hodgkin Lymphoma subtypes. In this retrospective study, we investigated the potential of semi-quantitative 2-[18F]fluoro-2-deoxy-D-glucose ([18F]FDG) PET/computed tomography (CT)-based parameters to differentiate between the PTLD morphological subtypes. Methods: 96 patients with histopathologically confirmed PTLD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The present study found that semi-quantitative measurement of metabolic parameters of lymph nodes and extranodal organs might be helpful in distinguishing M-HLH from NM-HLH. It's reported that the FDG uptake of lymph nodes is related with invasiveness of the disease (29). Okano et al found that increased SUV max -LN and SUV max -lesions indicated the lymphomaassociated HLH with cut-off value of 3.3, 5.5, respectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that semi-quantitative measurement of metabolic parameters of lymph nodes and extranodal organs might be helpful in distinguishing M-HLH from NM-HLH. It's reported that the FDG uptake of lymph nodes is related with invasiveness of the disease (29). Okano et al found that increased SUV max -LN and SUV max -lesions indicated the lymphomaassociated HLH with cut-off value of 3.3, 5.5, respectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to distinguish between PTLD-negative cases and nondestructive PTLD cases using SUVpeak due to the significant SUV overlap of the different subtypes. 13 Therefore, it is of significant interest to find an index that can distinguish PTLD-negative cases and nondestructive PTLD cases with high sensitivity, specificity, PPV, NPV, and accuracy; confirm or refute the clinical suspicion of PTLD; and identify suggestive lesions accessible for biopsy. This study reviewed and collected clinical and pathological data of pLT patients who underwent 18 F-FDG PET/CT and lymph node biopsy, explored the indicators that can effectively distinguish PTLD-negative cases and nondestructive PTLD cases, and evaluated their effects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the median peak standardized uptake value (SUVpeak) at the biopsy site of monomorphic PTLD is significantly higher than those of the polymorphic and nondestructive subtypes of PTLD. However, it is difficult to distinguish between PTLD‐negative cases and nondestructive PTLD cases using SUVpeak due to the significant SUV overlap of the different subtypes 13 . Therefore, it is of significant interest to find an index that can distinguish PTLD‐negative cases and nondestructive PTLD cases with high sensitivity, specificity, PPV, NPV, and accuracy; confirm or refute the clinical suspicion of PTLD; and identify suggestive lesions accessible for biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the median peak standardized uptake value (SUVpeak) at the biopsy site of monomorphic PTLD is significantly higher than those of the polymorphic and non-destructive subtypes of PTLD. However, it is difficult to distinguish between PTLD-negative cases and non-destructive PTLD cases using SUVpeak due to the significant SUV overlap of the different subtypes (13). Therefore, it is of significant interest to find an index that can distinguish PTLD-negative cases and non-destructive PTLD cases with high sensitivity, specificity, PPV, NPV, and accuracy; confirm or refute the clinical suspicion of PTLD; and identify suggestive lesions accessible for biopsy.…”
Section: Introductionmentioning
confidence: 99%